Indonesian EFL Students’ Tendencies in Writing Academic Essays - Hikmah Zalifah Putri; Bambang Yudi Cahyono (Soegijapranata Catholic University, 2020)
Abstract: This article aimed to find the tendencies exhibited by Indonesian students of English as a Foreign Language (EFL) students in writing an academic essay in English. A content analysis method is employed as the method of the study. The data of the study were the final draft of the essays written by EFL students of the English Department of a reputable university in East Java, Indonesia. The essays were analyzed by looking for the shared properties in each part of the essay. The data were analyzed by extracting the most common properties in each essay which are (a) thesis statement, (b) coherency, and (c) concluding remark. The results showed that the students tended to forget to use definite and indefinite articles, misuse the definite and indefinite articles with plural forms, to use of nouns and pronouns inconsistently, to use an English sentence with an Indonesian rhetoric pattern, and to not include a summary of the subtopics discussed in their body paragraphs. The result may be use as reference for future writing classes in Indonesia.